1986
DOI: 10.1007/bf02555402
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin-induced pseudomembranous colitis resulting in perforation of the sigmoid colon

Abstract: The seventh case of probable cefazolin-induced pseudomembranous colitis is reported. Perforation of the colon necessitated sigmoid resection. The postoperative course was protracted, and illustrates the difficulty of managing advanced pseudomembranous colitis when the oral route of antibiotic administration is not available. Although rare, pseudomembranous colitis related to cefazolin administration is a potentially fatal complication. The routine use of prophylactic antibiotics must be weighed against this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Patients who progressed to perforation always had a However, no study demonstrated a superior therapeutic effect of either tapering or pulse dose treatment [1, 21, high mortality rate [7,21,52,76,78,79,179,182,183].…”
Section: Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who progressed to perforation always had a However, no study demonstrated a superior therapeutic effect of either tapering or pulse dose treatment [1, 21, high mortality rate [7,21,52,76,78,79,179,182,183].…”
Section: Medical Treatmentmentioning
confidence: 99%
“…At present the primary surgical strategy is to resect the megacolon, uncontrolled bleeding, and perforation [17,48,76,78,130,[176][177][178][179]. In a 10-year prospective study, damaged bowel and create a protective proximal stoma [7,17].…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Treating with oral or intravenous antimicrobial regimens has been shown to be unsuccessful mainly due to inadequate concentration of the drug in the colon [57][58][59]. There is some evidence available that adding intra colonic vancomycin, as an alternative route, can be promising as in 57%-75% of patients [60,[61][62][63][64][65][66][67][68][69][70]. Intravenous metronidazole, in some circumstances, produces fecal concentrations greater than the MIC needed for C. difficile; therefore, it may be an effective therapy [71].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, addition of ICV, administered by rectal enema or long catheters, is an alternative regimen especially in severely ill patients who have not responded to first-line therapy or are not eligible for it [60,[61][62][63][64][65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation